Effect of water and gluten on physico-chemical properties and stability of ready to eat shelf-stable pasta. (15th March 2016) - Diantom, Agoura; Carini, Eleonora; Curti, Elena; Cassotta, Fabrizio; D'Alessandro, Alessandro; Vittadini, Elena
Highlights: The effect of water and gluten on shelf-stable pasta was studied during storage. Hardness and amylopectin retrogradation were reduced at higher moisture content. Gluten increased hardness and retrogradation but reduced the changes during storage. Increased molecular mobility was observed at higher moisture and gluten content. Abstract: A multi-analytical and multi-dimensional approach was used to investigate the effect of moisture and gluten on physico-chemical properties of shelf-stable ready to eat (RTE) pasta. Moisture and frozen water contents were not affected by formulation nor storage time. Hardness and retrograded amylopectin significantly increased during storage in all samples, more markedly in pasta with the lowest moisture content. Higher amounts of water and gluten reduced pasta hardening and contributed to control RTE pasta quality. 1 H FID became steeper in all samples during storage, but no effect of high moisture and gluten levels was observed on the mobility of these protons. Three proton T 2 populations were observed (population C, population D and population E). Population C and D were not resolved during all storage. 1 H T 2 relaxation time of the most abundant population (population E) shifted to shorter times and the amount of protons increased during storage, more importantly in the samples with lower moisture and gluten content.